Az összekapcsoltság hatása a rendszerkockázatra homogén bankrendszerben - Péter Csóka; Tamás Kiss (Hungarian Academy of Sciences, Institute of Economics, 2015)
– The most fundamental form of systemic risk in modern financial networks is contagion. In this article we describe a homogeneous banking system (banks with identical preferences and the same size of total assets) with interconnectedness: banks own shares in each others' assets. Using these simplifications we derive an analytically tractable indicator for systemic risk based on the expected loss of banks in case of a default in the system. Analyzing this indicator we find that increasing the volatility of the assets and decreasing the level of equity both raises systemic risk. Furthermore, interconnectedness in the system has an ambiguous effect. On the one hand it increases the diversification effect because banks can cover losses by holding assets of other banks. On the other hand if the connection is strong at the beginning, increasing it further induces additional systemic risk by raising the probability of contagion.
Keywords: C70; G18; G20; 330; systemic risk; interbank market; financial contagion; game theory